Strategi Peningkatan Kepatuhan Pajak Melalui Pelatihan Brevet Pajak: Peran Motivasi dan Literasi Akuntansi - Setianan, Andreas Ronald; Andika, Andika; Putri, Wika Harisa; Lestari, Puji (Politeknik Ganesha Medan, 2024)
In Indonesia, the obligation to pay taxes regulated through Law Number 28 Year 2007 is critical in the country’s fiscal structure. The self-assessment system recognizes the vital role of taxpayers in ensuring tax compliance and contribution. However, significant challenges, such as tax evasion, late payments, and incidents of incomplete payments, highlight the need to understand more deeply the factors that influence tax compliance. In addition, tax brevet training (PBP) is considered strategic to improve tax understanding and compliance, although accounting students’ interest in this program is not optimal. This study explores the moderating role of accounting literacy in the relationship between economic and quality motivation and its impact on accounting students’ interest in joining the PBP program. 200 data were collected using a quantitative approach through a questionnaire survey distributed to accounting students in Yogyakarta through Google Forms. Variable ratings were conducted using a Likert scale, while data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The study results show that both quality motivation and economic motivation significantly affect accounting students’ interest in participating in the PBP program. However, accounting literacy negatively moderates the effect of motivation on student interest. Furthermore, accounting literacy has no significant influence on increasing the impact of economic motivation on interest in joining the tax brevet. Based on the R Square test results, the effect of quality motivation and economic motivation moderated by accounting literacy has a moderate effect on accounting students’ interest in joining the PBP program, with a value of 0.682.